Multistage relative humidity control strategy enhances energy and exergy efficiency of convective drying of carrot cubes. (March 2020) - Yu, Xian-Long; Zielinska, Magdalena; Ju, Hao-Yu; Mujumdar, Arun S.; Duan, Xu; Gao, Zhen-Jiang; Xiao, Hong-Wei
Highlights: Energy-saving process of hot air drying based on process control was proposed. A mathematical model was developed by taking relative humidity into consideration. Numerical model demonstrate the exergy loss of each component during drying. The relationship between relative humidity and energy consumption were explored. Abstract: Industrial drying is one of the most energy intensive unit operations encountered in most industrial sectors. Therefore, much effort has been devoted to energy savings in drying. Most methods applied to convective drying are based on heat recovery from dryer exhaust. However, there are major limitations on how much of the energy can be recovered cost-effectively. Here a new concept based on the relative humidity (RH) control of convective drying of carrot cubes was evaluated with the purpose of enhancing the energy and exergy efficiency of drying. Numerical simulations of heat and mass transfer were performed to investigate hot air drying behavior of carrot cubes. The model fitted well the moisture ratio and the material temperature data with average relative errors of 6.5% and 0.8%, respectively. Results show that both the energy loss caused by exhaust air and the irreversibility loss of thermodynamic process decreased with increase in RH of the drying medium from 4% to 40%. Multistage relative humidity control strategy improved both the drying rate and exergy efficiency. Among the tested schemes, the three-stage RH control strategy, i.e. (1) RH of 40% for 2 h, (2) RH of 20% for 2 h and (3) RH of 4% for 3.5 h was found to be the strategy with the highest exergy efficiency (53.3%). It was almost three times higher than that for constant 4% RH values.